Creating Shared Value for Millennial Age: Case Study of PT. Nestle Indonesia - Alan Christian Singkali; Gatot Sasongko (Jurnal Studi Sosial dan Politik, 2022)
This study aims to describe CSV based on community empowerment, especially in the millennial generation. The research method used is qualitative with a case study approach. Data collection techniques used interviews. Interviews were conducted with two key informants, namely Sahlan Junaedy (FFPM staff) and Pariatmoko (MPDD staff) Data processing uses triangulation to obtain valid and credible information. The results showed that Nestle's CSV in community empowerment programs, young people or millennials were quite involved. Among other things, clean water supply programs and nutrition programs such as: young people are involved in the provision of clean water including managing HIPPAM, school children in nutrition programs, and others. The recommendation in this study is that the presence of CSV from Nestle has an influence on the millennial generation, especially in the sustainability of smallholder farms, especially for young breeders.